TINJAUAN YURIDIS TERKAIT PENGHAPUSAN PERAN JUSTICE COLLABORATOR DALAM SYARAT PENGURANGAN MASA PIDANA DIKAITKAN DENGAN TUJUAN PEMIDANAAN DALAM TINDAK PIDANA KORUPSI - Nicho Samuel Arganatha Rajagukguk; Erdiansyah Erdiansyah; Tengku Arif Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Arrangements for granting remissions or conditional release in cases of corruption priorto the decision number 28P/HUM/2021 have special conditions or differences in obtainingremissions or parole compared to other general crimes. This is regulated in GovernmentRegulation Number 99 of 2012 concerning Requirements and Procedures for theImplementation of the Rights of Correctional Families. This special condition requires thatcorruption convicts become justice collaborators or are willing to work with law enforcementagencies to help uncover the crimes they have committed. However, after the decision has beenmade, remission and parole are given more easily because there are no special conditions, thiscan reduce the expected deterrent effect and eliminate substance from the correctional system.The purpose of this research is to find out the elimination of the role of justice collaborator interms of reducing the term of imprisonment in accordance with the purpose of sentencing andto look at legal considerations in deciding to delete the article which contains specialconditions for obtaining remission for corruptors.This research is normative legal research supported by secondary data, carried out bymaking library materials the main focus. It is also called doctrinal legal research, namely legalresearch that uses data based on library research by taking excerpts from reading books, orsupporting books that have something to do with the problem to be studied. Thus this studyuses secondary data sources consisting of primary, secondary, and tertiary legal materials.This study also used qualitative data analysis and produced descriptive data.From the results of the discussion and research conducted, several conclusions wereobtained, namely: First, the elimination of the role of justice collaborators in terms of reducingprison terms is not in accordance with the objectives of punishment which wants to provide adeterrent effect and guidance for perpetrators who commit crimes. If there are no suchconditions, it will make it easier for corruption convicts to get remissions or parole. Second,there are 4 important points of legal considerations taken by the author and the legalconsiderations that have been examined have several deficiencies that result in mistakes thatremove special requirements for corruption.Keywords: Justice Collaborator – Corruption - Criminalization